Amino acid sensing and activation of mechanistic target of rapamycin complex 1: implications for skeletal muscle. Issue 1 (January 2016) - Ham, Daniel J.; Lynch, Gordon S.; Koopman, René
Abstract : Purpose of review: This article evaluates recent studies on the mechanisms involved in sensing changes in amino acid availability and activation of the mechanistic target of rapamycin complex 1 (mTORC1). Recent findings: mTORC1 is sensitive to changes in amino acid availability and a well known regulator of protein turnover. The mechanisms of amino acid sensing and mTORC1 signaling are emerging with multiple potential sensors (e.g., solute carrier family 38, member 9, lysosomal protein transmembrane 4 beta/solute carrier family 7, member 5-solute carrier family 3, member 2) and signal transducers (e.g., Sestrins, ADP-ribosylation factor 1, and microspherule protein 1) identified. Studies in various cell lines have unveiled the importance of the lysosome in amino acid sensing and signal transmission. Summary: Recent discoveries in amino acid sensing highlight a complex scenario, whereby mTORC1 is not merely sensitive to some amino acids and not others, but where specific amino acids are sensed by specific pathways under specific conditions. The physiological purpose of such an arrangement remains to be unraveled, but it would allow mTORC1 to precisely regulate growth during different metabolic conditions. Understanding the mechanisms responsible for sensing amino acid availability and regulating mTORC1 activity is an important prerequisite for the development of nutritional strategies to combat skeletal muscle wasting disorders.